Single crystal film and preparation method and application thereof
By introducing a conductive layer into the single-crystal thin film, the polarization defects and high optical loss problems of nanoscale oxide single-crystal thin films are solved, and a high-performance single-domain single-crystal thin film suitable for electro-optic modulators is prepared.
Patent Information
- Application Number
- CN202411384910.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
Existing technologies for preparing nanoscale oxide single-crystal thin films are prone to polarization defects and high optical losses, making it difficult to meet the requirements of miniaturized and high-performance communication devices.
A conductive layer is introduced into the single-crystal thin film. The resistivity of the conductive layer is less than 100 Ωcm and the transparent window is 500 nm-1.6 μm. The conductive layer can quickly conduct away the charge generated in the pyroelectric thin film during high-temperature annealing, eliminate polarization defects, and reduce optical loss.
A single-crystal thin film with a single domain ratio of not less than 95% was achieved, reducing absorption loss and providing an electro-optic modulator with large bandwidth, low half-wave voltage and high speed.
Smart Images

Figure CN119283446A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a single crystal film, in particular to a single crystal film and a preparation method and application thereof, belonging to the technical field of semiconductor materials. Background Art
[0002] Oxide single crystals such as lithium niobate (LN), lithium tantalate (LT), and quartz, as piezoelectric materials, are widely used in materials for components such as surface acoustic wave (SAW) filters due to their good electromechanical coupling coefficient, which can enable filters to achieve high bandwidth characteristics. The traditional polishing process can obtain oxide single crystal thin films of several microns to tens of microns, but with the development trend of miniaturization of communication equipment, the volume of parts in the equipment is also required to be further miniaturized and high-performance, so the method of preparing nanometer-level thickness thin films using smart peeling technology is also used to prepare nanometer-level thickness oxide single crystal thin films.
[0003] Smart stripping technology mainly uses light ions to bombard the wafer, such as H + 、He + etc., so that charged ions enter the wafer and form an ion implantation layer inside the wafer, and then after a heat treatment process, the single crystal film is peeled off from the original wafer at the location of the ion implantation layer. However, during the preparation process, since a higher energy, such as 500KeV, is required to bombard the oxide single crystal wafer, more defects will be generated in the single crystal film. Therefore, it is necessary to select a suitable temperature to anneal the obtained nano-scale single crystal film in order to eliminate the defects caused by ion implantation.
[0004] Taking lithium niobate crystal as an example, lithium niobate crystal has a very high pyroelectric coefficient, up to 4×1 0-5 C / m 2 K, and due to its high resistivity (10 13 Ωcm or more), in the process of eliminating the defects produced by the smart stripping technology by annealing, with the change of temperature, a large amount of static charge is easily accumulated on the wafer surface. Although these static charges can be spontaneously released in a natural state, the release process is very slow, so the formed charges will accumulate between the substrate and the pyroelectric film, thereby forming an electric field. In this way, the spontaneous polarization vector Ps of the Z-cut lithium niobate wafer can easily undergo polarization reversal under the action of the electric field, which eventually leads to the formation of polarization defects in the Z-cut lithium niobate wafer during the annealing process. Specifically, multiple polarization spots appear on the surface of the Z-cut lithium niobate wafer. These polarization spots may have no effect on the ferroelectric properties of the single crystal film, but will increase the surface roughness of the single crystal film, thereby affecting subsequent thin film etching, electrode processing and other processes, and then leading to an increase in the absorption loss of the single crystal film. Devices made using such films also usually have high optical losses and are difficult to meet the corresponding performance requirements.
[0005] In order to overcome the polarization defects of lithium niobate wafers, the existing technology is to make electrodes on both ends of the crystal, heat it to above the Curie temperature, pass current, and then gradually cool it down. However, this method is not suitable for making thin film substrate materials because each piece needs to have electrodes on both sides, and the cost of mass production is high and the process is complicated, so it is impossible to achieve mass production. In addition, due to the large difference in thermal expansion coefficients between silicon substrates and pyroelectric crystals such as lithium niobate, the film is very likely to break when heated above the Curie temperature.
[0006] Based on the above shortcomings, those skilled in the art are in urgent need of developing a single-crystal thin film with nanometer thickness that can avoid polarization defects and has a simple preparation process. Summary of the invention
[0007] The present invention provides a single crystal film, which can avoid polarization defects and eliminate polarization reversal spots generated on the surface of the single crystal film due to polarization reversal of pyroelectric crystals, so that a single crystal film with a single domain rate of not less than 95% can be produced, thereby reducing the absorption loss of the single crystal film, and the preparation process of the single crystal film is simple.
[0008] The invention provides a method for preparing a single crystal film. The method can prepare a single crystal film with a single domain rate of not less than 95%, and the method has simple process, easy operation and low cost.
[0009] The present invention also provides an electro-optic modulator, which is prepared based on the above-mentioned single crystal film, and has the advantages of large bandwidth, low half-wave voltage, high speed, etc.
[0010] The present invention provides a single crystal film, wherein the single crystal film comprises a substrate layer, an isolation layer, a conductive layer and a pyroelectric crystal film layer which are stacked in sequence, the resistivity of the conductive layer is less than 100Ωcm, and the transparent window of the conductive layer is 500nm-1.6μm.
[0011] The single crystal film as described above, wherein the thickness of the conductive layer is 5-50 nm; and / or the surface roughness of the conductive layer is not higher than 0.5 nm.
[0012] The single crystal thin film as described above, wherein the material of the conductive layer includes one of zinc oxide and titanium oxide.
[0013] The single crystal film as described above, wherein the refractive index of the material used for the isolation layer is not greater than the refractive index of the material used for the pyroelectric crystal film layer; and / or the surface roughness of the isolation layer is not greater than 0.5 nm.
[0014] The single crystal film as described above, wherein the material of the substrate layer includes silicon; and / or the material of the isolation layer includes one of silicon dioxide and silicon nitride; and / or the material of the pyroelectric crystal film layer includes one of lithium niobate and lithium tantalate.
[0015] The single crystal thin film as described above, wherein the thickness of the substrate layer is 0.1-1 mm;
[0016] And / or, the thickness of the isolation layer is 500nm-5μm;
[0017] And / or, the thickness of the pyroelectric crystal thin film layer is 50nm-5μm.
[0018] The present invention provides a method for preparing the single crystal thin film as described above, which comprises the following steps:
[0019] 1) sequentially arranging an isolation layer and a conductive layer on the substrate layer to obtain an intermediate;
[0020] Wherein, the resistivity of the conductive layer is less than 100Ωcm, and the transparent window of the conductive layer is 500nm-1.6μm;
[0021] 2) injecting ions into the pyroelectric crystal material to obtain an ion bombardment body; the ion bombardment body comprises a film layer, a separation layer and a residual material layer stacked in sequence;
[0022] 3) bonding the thin film layer in the ion bombardment body and the conductive layer in the intermediate body, and then peeling off the separation layer and the residual material layer to obtain a precursor;
[0023] 4) performing heat preservation treatment and polishing treatment on the precursor to obtain the single crystal film.
[0024] The method for preparing the single crystal thin film as described above, wherein the ion implantation energy of the ion implantation treatment is 30KeV-5MeV, and the ion implantation dose is 1×10 15 -1×10 17 ions / cm 2 .
[0025] The method for preparing a single crystal thin film as described above, wherein the separation layer and the residual material layer are peeled off by annealing, wherein the annealing temperature is 150-400° C. and the annealing time is 0.5-48 hours.
[0026] The present invention also provides an electro-optic modulator, wherein the raw material of the electro-optic modulator includes the single crystal film as described above.
[0027] The present invention arranges a conductive layer between the pyroelectric crystal film layer and the isolation layer, and controls the resistivity and transparent window of the conductive layer, so that the conductive layer has high conductivity, can quickly conduct away the charge generated at the bonding interface during the high-temperature annealing process of the pyroelectric film to repair damage, eliminates the possibility of polarization defects in the single crystal film, thereby improving the single domain rate of the single crystal film, and at the same time can avoid introducing additional electrodes and other materials with high optical absorption into the single crystal film, ensuring that the pyroelectric film has low absorption loss in the commonly used optical bands, thereby achieving the low optical loss characteristics of the single crystal film, and the single crystal film can be manufactured through a relatively simple process with low cost.
[0028] The present invention can prepare a single crystal film with a conductive layer through the single crystal film preparation method, and the conductive layer can quickly conduct away the charge generated at the bonding interface during the high-temperature annealing process of the pyroelectric film to repair damage, thereby eliminating the possibility of polarization defects in the single crystal film. In addition, the preparation method has a simple process, is easy to operate, and each material is easy to obtain, has low equipment requirements, and is low in cost.
[0029] The present invention also provides an electro-optic modulator, which has the characteristics of low optical loss, large bandwidth, low half-wave voltage, high rate and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the structure of a single crystal thin film;
[0031] Figure 2 This is a resistivity test diagram of the conductive layer in the single crystal thin film of Example 1;
[0032] Figure 3 This is a refractive index test diagram of the single crystal film of Example 1.
[0033] Description of reference numerals:
[0034] 1-pyroelectric crystal thin film layer;
[0035] 2-conductive layer;
[0036] 3-Isolation layer;
[0037] 4-Substrate layer. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The present invention provides a single crystal thin film, such as Figure 1 As shown, it includes a substrate layer 4, an isolation layer 3, a conductive layer 2 and a pyroelectric crystal film layer 1 stacked in sequence, the resistivity of the conductive layer is less than 100Ωcm, and the transparent window of the conductive layer is 500nm-1.6μm.
[0040] The single crystal film of the present invention has a four-layer structure, which comprises a substrate layer, an isolation layer, a conductive layer and a pyroelectric crystal film layer which are stacked in sequence.
[0041] The present invention is not limited to a specific selection of the material of the substrate layer, as long as the potential can be fixed and charge drift can be prevented.
[0042] The present invention does not limit the specific selection of the material of the isolation layer, as long as it can prevent the single crystal film from cracking or falling off due to the stress in the single crystal film.
[0043] The present invention does not limit the specific selection of the material of the conductive layer, as long as it has high conductivity and a wide transparent window.
[0044] The present invention does not limit the specific selection of the material of the pyroelectric crystal thin film layer, as long as the material has the pyroelectric effect.
[0045] The resistivity of the conductive layer of the present invention is less than 100Ωcm, for example, 5Ωcm, 10Ωcm, 15Ωcm, 20Ωcm, 25Ωcm, 30Ωcm, 35Ωcm, 40Ωcm, 45Ωcm, 50Ωcm, 55Ωcm, 60Ωcm, 65Ωcm, 70Ωcm, 75Ωcm, 80Ωcm, 85Ωcm, 90Ωcm or 95Ωcm, etc. When the resistivity of the conductive layer is less than 100Ωcm, the conductive layer has high conductivity.
[0046] The transparent window of the conductive layer is 500nm-1.6μm, for example, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm or 1.6μm, etc. The transparent window of the present invention means that when the wavelength of visible light is in the range of 500nm-1.6μm, the conductive layer is transparent, which can reduce the absorption loss of the conductive layer in the commonly used optical band.
[0047] According to the above scheme provided by the present invention, the single crystal film can avoid polarization defects, thereby improving the monodomain rate of the single crystal film. The inventor analyzed this principle and believed that the reason may be that, on the one hand, the conductive layer is placed between the pyroelectric crystal film layer and the isolation layer. The conductive layer has high conductivity and can quickly conduct away the charge generated at the bonding interface during the high-temperature annealing process of the pyroelectric film to repair damage, eliminating the possibility of polarization defects in the single crystal film, ensuring the monodomain of the pyroelectric film, thereby improving the monodomain rate of the single crystal film; on the other hand, the conductive layer has a good transparent effect in the commonly used visible light band, avoiding the introduction of additional electrodes and other materials with large optical absorption into the single crystal film, ensuring that the pyroelectric film has low absorption loss in the commonly used optical band, thereby achieving the low optical loss characteristics of the single crystal film, and the single crystal film can be made through a relatively simple process with low cost.
[0048] Specifically, the single crystal thin film of the present invention is subjected to a thin film resistivity test using extended resistivity to obtain the resistivity of the conductive layer.
[0049] In a specific embodiment, the thickness of the conductive layer is 5-50 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, etc. When the thickness of the conductive layer is within the above range, the thickness of the conductive layer is low, which can improve the charge accumulation of the pyroelectric crystal film, and can avoid excessive absorption and scattering of light due to excessive thickness of the conductive layer, resulting in a decrease in the optical performance of the single crystal film, thereby improving the single domain type of the single crystal film, and further reducing the absorption loss of the single crystal film.
[0050] In a specific embodiment, the surface roughness of the conductive layer is not higher than 0.5 nm, for example, 0.1 nm, 0.2 nm, 0.3 nm, 0.4 nm or 0.5 nm. When the surface roughness of the conductive layer is within the above range, it is beneficial to the subsequent bonding of the conductive layer and the pyroelectric crystal film layer, and can increase the contact area between the conductive layer and the pyroelectric crystal film layer, which is beneficial to the rapid release of the charge of the pyroelectric crystal film, avoiding the polarization defects of the single crystal film, thereby reducing the surface roughness of the single crystal film, and further reducing the absorption loss of the single crystal film. Preferably, the surface roughness of the conductive layer is 0.2-0.3 nm.
[0051] Specifically, the surface roughness of the conductive layer under the single crystal thin film of the present invention is tested using an atomic force microscope (tested before bonding) to obtain the roughness of the conductive layer.
[0052] In a specific embodiment, the material of the conductive layer includes one of zinc oxide and titanium oxide. When the conductive layer is made of the above materials, the conductive layer has high conductivity and a wide transparent window, which is conducive to preparing a single crystal film with low polarization defects, thereby reducing the absorption loss of the single crystal film.
[0053] In a specific embodiment, the refractive index of the material used for the isolation layer is not greater than the refractive index of the material used for the pyroelectric crystal thin film layer, so that the light field can be confined to the high-refractive-index pyroelectric crystal thin film layer for propagation, and the light field is prevented from leaking into the isolation layer and causing scattering loss of the light signal, thereby reducing the optical loss of the single crystal thin film. For example, the refractive index of the material used for the isolation layer can be selected to be 1.45, 1.47 or 2, etc.
[0054] Specifically, the single crystal film of the present invention is tested for refractive index using a prism coupler to obtain the refractive index of the isolation layer and the refractive index of the pyroelectric crystal film layer.
[0055] In a specific embodiment, the surface roughness of the isolation layer is not greater than 0.5 nm, for example, 0.1 nm, 0.2 nm, 0.3 nm, 0.4 nm or 0.5 nm. When the surface roughness of the isolation layer is within the above range, it is beneficial to arrange the conductive layer on the isolation layer, and can increase the adhesion effect between the isolation layer and the conductive layer, and can improve the stability of the single crystal film. Preferably, the surface roughness of the isolation layer is 0.2-0.3 nm.
[0056] In a specific embodiment, the material of the substrate layer includes silicon. Silicon material has a mature process system, is easy to obtain, and is inexpensive. In addition, it is easy to operate by setting an isolation layer on the silicon material, which is conducive to the subsequent preparation of single crystal thin films and lays a foundation for the widespread preparation of single crystal thin films.
[0057] In a specific embodiment, the material of the isolation layer includes one of silicon dioxide and silicon nitride. When the material of the isolation layer is selected from the above materials, the refractive index of the isolation layer is not greater than the refractive index of the pyroelectric crystal thin film layer, which is conducive to better confining the optical signal in the high-refractive-index pyroelectric crystal thin film layer, thereby reducing the optical loss of the single crystal thin film.
[0058] In a specific embodiment, the material of the pyroelectric crystal film layer includes one of lithium niobate and lithium tantalate. These materials have good electro-optic coefficients and high refractive indexes, and when applied to single crystal films, they can make the single crystal films have high electro-optic modulation efficiency and low optical loss.
[0059] In a specific embodiment, the thickness of the substrate layer is 0.1-1 mm, for example, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm, etc. When the thickness of the substrate layer is within the above range, the substrate layer has a good supporting effect on the pyroelectric crystal film layer, and the substrate layer has a good thermal conductivity effect.
[0060] In a specific embodiment, the thickness of the isolation layer is 500nm-5μm, for example, 500nm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm or 5μm. When the thickness of the isolation layer is within the above range, the optical signal can be better confined in the pyroelectric crystal thin film layer, so that the single crystal thin film achieves low optical loss.
[0061] In a specific embodiment, the thickness of the pyroelectric crystal film layer is 50nm-5μm, for example, 50nm, 100nm, 200nm, 500nm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm or 5μm, etc. When the thickness of the pyroelectric crystal film layer is within the above range, the optical signal can be partially or completely accommodated, and more optical signals can be ensured to be absorbed by the single crystal film, reducing the loss of the optical signal, thereby reducing the optical loss of the single crystal film.
[0062] The present invention provides a method for preparing the above-mentioned single crystal thin film, comprising the following steps:
[0063] 1) sequentially disposing an isolation layer and a conductive layer on a substrate layer to obtain an intermediate;
[0064] The resistivity of the conductive layer is less than 100Ωcm, and the transparent window of the conductive layer is 500nm-1.6μm;
[0065] 2) injecting ions into the pyroelectric crystal material to obtain an ion bombardment body; the ion bombardment body includes a film layer, a separation layer and a residual material layer stacked in sequence;
[0066] 3) bonding the thin film layer in the ion bombardment body and the conductive layer in the intermediate body, and then peeling off the separation layer and the residual material layer to obtain a precursor;
[0067] 4) The precursor is subjected to heat preservation treatment and polishing treatment to obtain a single crystal film.
[0068] Specifically, in step 1), an isolation layer is disposed on the substrate layer, and then a conductive layer is disposed on the isolation layer to obtain an intermediate, which includes the substrate layer, the isolation layer and the conductive layer stacked in sequence.
[0069] The present invention does not limit the specific selection of the material of the substrate layer, which can be selected according to actual needs. Generally, it is a material with a mature process system, such as silicon, amorphous silicon, etc.
[0070] The present invention does not limit the specific selection of the material of the isolation layer, and the material can be selected according to actual needs. For example, amorphous materials such as silicon dioxide and silicon nitride can be used.
[0071] The present invention does not limit the specific selection of the material of the conductive layer, as long as the resistivity of the conductive layer is less than 100 Ωcm and the transparent window is 500 nm-1.6 μm.
[0072] The present invention does not limit the specific method of setting the isolation layer on the substrate layer. For example, the isolation layer can be deposited on the substrate layer by thermal oxidation, PECVD, LPCVD, CVD, etc. In addition, the deposited isolation layer can be annealed to eliminate impurity ions in the deposited isolation layer to reduce absorption loss.
[0073] The present invention does not limit the specific method of arranging the conductive layer on the isolation layer. For example, the conductive layer can be deposited on the isolation layer by magnetron sputtering, PECVD, CVD, molecular beam epitaxy, etc. Moreover, the deposited conductive layer can be annealed to eliminate impurity ions in the deposited conductive layer to reduce absorption loss.
[0074] The present invention also controls the surface roughness of the isolation layer and the conductive layer. The present invention does not limit the method for controlling the surface roughness. For example, chemical mechanical polishing can be used to reduce the surface roughness.
[0075] Step 2) ion implantation is performed on the pyroelectric crystal material to implant ions into the pyroelectric crystal material to obtain an ion bombardment body, which includes a film layer, a separation layer and a residual material layer stacked in sequence.
[0076] The present invention does not limit the specific selection of pyroelectric crystal materials, and the selection can be made according to actual needs. For example, electro-optical materials such as lithium niobate and lithium tantalate can be selected.
[0077] The present invention does not limit the selection of implanted ions, which may be selected according to actual needs, for example, helium ions, hydrogen ions, etc. may be selected.
[0078] The present invention does not limit the implantation energy and implantation dosage of ion implantation, as long as an ion bombardment body including a thin film layer, a separation layer and a residual material layer can be obtained.
[0079] Step 3), bonding the thin film layer in the ion bombardment body and the conductive layer in the intermediate body to obtain a bonded body including a substrate layer, an isolation layer, a conductive layer, a thin film layer, a separation layer and a residual material layer stacked in sequence, and then peeling off the separation layer and the residual material layer on the structure to obtain a precursor.
[0080] The present invention does not limit the specific method of bonding treatment, which can be selected according to actual needs, such as using room temperature bonding technology.
[0081] The present invention does not limit the method of peeling off the separation layer and the residual material layer, and the method can be selected according to actual needs, for example, annealing treatment can be used.
[0082] Step 4), the thin film layer on the precursor is subjected to insulation treatment and polishing treatment in sequence to obtain a single crystal thin film.
[0083] The present invention does not limit the specific parameters of the heat preservation treatment, which can be selected according to actual needs. For example, heat preservation at 500° C. for 4 hours can eliminate the defects caused by ion implantation.
[0084] The present invention does not limit specific parameters of the polishing process, and the parameters can be selected according to actual needs, so as to achieve a single crystal film with a small thickness.
[0085] The present invention can prepare a single crystal film with a conductive layer through the single crystal film preparation method, and the conductive layer can quickly conduct away the charge generated at the bonding interface during the high-temperature annealing process of the pyroelectric film to repair damage, thereby eliminating the possibility of polarization defects in the single crystal film. In addition, the preparation method has a simple process, is easy to operate, and each material is easy to obtain, has low equipment requirements, and is low in cost.
[0086] In a specific embodiment, the ion implantation energy of the ion implantation process is 30 KeV-5 MeV, for example, 30 KeV, 100 KeV, 500 KeV, 1 MeV, 2 MeV, 3 MeV, 4 MeV or 5 MeV, and the ion implantation dose is 1×10 15 -1×10 17 ions / cm 2 , for example, 1×10 15 ions / cm 2 , 3×10 15 ions / cm 2 ,7×10 15 ions / cm 2 , 1×10 16 ions / cm 2 , 3×10 16 ions / cm 2 ,7×10 16 ions / cm 2 or 1×10 17 ions / cm 2When the ion implantation energy and ion implantation dosage of the ion implantation process are within the above range, an ion bombardment body including a thin film layer, a separation layer and a residual material layer can be prepared, which is beneficial to the subsequent preparation of a single crystal thin film and can avoid the waste of ion implantation energy and ion implantation dosage, thereby saving costs.
[0087] In a specific embodiment, the separation layer and the residual material layer are peeled off by annealing treatment, wherein the annealing temperature is 150-400°C, such as 150°C, 200°C, 250°C, 300°C, 350°C or 400°C, and the annealing time is 0.5-48h, such as 0.5h, 1h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h or 48h, etc. When the above annealing treatment is adopted, the separation layer and the thin film layer can be effectively separated, so that the separation layer and the residual material layer are peeled off from the bonded body, thereby obtaining a single crystal thin film, and the annealing treatment is easy to operate and has low cost requirements.
[0088] The present invention also provides an electro-optic modulator, which is prepared by using the above-mentioned single crystal film. The prepared electro-optic modulator has the advantages of large bandwidth, low half-wave voltage, high speed, etc.
[0089] Hereinafter, the present invention will be further described in detail through specific examples.
[0090] Example 1
[0091] The preparation process of the single crystal thin film provided in this embodiment includes the following steps:
[0092] 1. Prepare a single crystal silicon substrate wafer with a size of 4 inches, a thickness of 0.525 mm and a smooth surface, clean the smooth surface of the substrate wafer, and use a thermal oxidation process to prepare a layer of silicon dioxide as an isolation layer on the single crystal silicon substrate wafer. The thickness of the isolation layer is 4.7 μm and the roughness of the silicon dioxide is 0.2 nm.
[0093] 2. The silicon dioxide layer on the silicon substrate wafer obtained in step 1 is cleaned again, and a zinc oxide film is prepared on the silicon dioxide layer by CVD as a conductive layer, and the thickness of the conductive layer is 180 nm. The conductive layer is then annealed and chemically mechanically polished to ensure that the roughness of the zinc oxide is 0.2 nm, and the thickness of the conductive layer after polishing is 50 nm.
[0094] 3. Prepare a 4-inch lithium niobate wafer with a thickness of 0.525 mm and a smooth surface, and use ion implantation to implant helium ions (He+) into the lithium niobate wafer. The helium ion implantation energy is 300 KeV and the dose is 5×10 16 ions / cm 2, forming a lithium niobate wafer with a three-layer structure of a thin film layer, a separation layer and a residual layer, and the thickness of the thin film layer is 940nm.
[0095] 4. Using a plasma bonding method, the ion-implanted lithium niobate thin film layer is bonded to the silicon wafer zinc oxide layer obtained in step 2 to obtain a bonded body. The bonded body is then annealed at 150° C. for 48 hours to obtain a precursor.
[0096] 5. The precursor was kept at 500°C for 4 hours, and then the precursor was polished to remove the damage layer on the surface of the film caused by injection, and the film layer was thinned to 710nm to obtain a single crystal film.
[0097] For single crystal thin films, the resistivity of the conductive layer is tested using extended resistivity, such as Figure 2 As shown, the resistivity of the conductive layer is 100 ohm-cm.
[0098] The refractive index of single crystal thin film is tested using a prism coupler, such as Figure 3 As shown, at a wavelength of 632.8 nm, the refractive index of silicon dioxide used in the isolation layer is 1.4577, and the refractive index of lithium niobate used in the pyroelectric crystal film layer is 2.2863.
[0099] In summary, the single crystal film provided by the present invention has a conductive layer with low resistivity, which can quickly conduct away the charge generated at the bonding interface of the pyroelectric film during high-temperature annealing to repair damage, thereby improving the single domain rate of the single crystal film.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A single crystal thin film, characterized in that: The single crystal film comprises a substrate layer, an isolation layer, a conductive layer and a pyroelectric crystal film layer which are stacked in sequence. The resistivity of the conductive layer is less than 100Ωcm, and the transparent window of the conductive layer is 500nm-1.6μm.
2. The single crystal thin film according to claim 1, characterized in that: The thickness of the conductive layer is 5-50 nm; and / or the surface roughness of the conductive layer is not higher than 0.5 nm.
3. The single crystal thin film according to claim 1 or 2, characterized in that: The material of the conductive layer includes one of zinc oxide and titanium oxide.
4. The single crystal thin film according to any one of claims 1 to 3, characterized in that: The refractive index of the material used for the isolation layer is not greater than the refractive index of the material used for the pyroelectric crystal thin film layer; and / or the surface roughness of the isolation layer is not greater than 0.5 nm.
5. The single crystal thin film according to any one of claims 1 to 4, characterized in that: The material of the substrate layer includes silicon; and / or the material of the isolation layer includes one of silicon dioxide and silicon nitride; and / or the material of the pyroelectric crystal film layer includes one of lithium niobate and lithium tantalate.
6. The single crystal thin film according to any one of claims 1 to 5, characterized in that: The thickness of the substrate layer is 0.1-1 mm; And / or, the thickness of the isolation layer is 500nm-5μm; And / or, the thickness of the pyroelectric crystal thin film layer is 50nm-5μm.
7. A method for preparing a single crystal thin film according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) sequentially arranging an isolation layer and a conductive layer on the substrate layer to obtain an intermediate; Wherein, the resistivity of the conductive layer is less than 100Ωcm, and the transparent window of the conductive layer is 500nm-1.6μm; 2) injecting ions into the pyroelectric crystal material to obtain an ion bombardment body; the ion bombardment body comprises a film layer, a separation layer and a residual material layer stacked in sequence; 3) bonding the thin film layer in the ion bombardment body and the conductive layer in the intermediate body, and then peeling off the separation layer and the residual material layer to obtain a precursor; 4) performing heat preservation treatment and polishing treatment on the precursor to obtain the single crystal film.
8. The method for preparing a single crystal thin film according to claim 7, characterized in that: The ion implantation energy of the ion implantation treatment is 30KeV-5MeV, and the ion implantation dose is 1×10 15 -1×10 17 ions / cm 2 .
9. The method for preparing a single crystal thin film according to claim 7 or 8, characterized in that: The separation layer and the residual material layer are peeled off by annealing treatment, wherein the annealing temperature is 150-400° C. and the annealing time is 0.5-48 hours.
10. An electro-optic modulator, characterized in that: The raw material of the electro-optic modulator includes the single crystal thin film according to any one of claims 1-5.
Citation Information
Patent Citations
Piezoelectric device and method of manufacturing piezoelectric device
CN103718457A
Single crystal thin film composite substrate and manufacturing method thereof
CN110828298A
Silicon-based lithium tantalate single crystal thin film substrate with bottom electrode and preparation method and application of silicon-based lithium tantalate single crystal thin film substrate
CN110867381A
Preparation method of pyroelectric composite film
CN116669523A
Single crystal film and optical waveguide structure for high-performance electro-optical modulator
CN118091993A